Identifying prognosis factors of pathological staging among colorectal patients using ordinal logistic regression model - Md Ghani, Nor Azura; Mohd Ghani, Khairul Asri; Mahmud, Zamalia; Abu Hassan, Nurhasniza Idham; Mohamed Ramli, Norazan
Colorectal cancer is known as one of the cancer disease that is often related to dietary habits, age, sex, and family history. Laparoscopic resection is one of the recent techniques used to treat colorectal cancer patients. The main objective of this paper is to model the success of laparoscopic resection of colorectal cancer patients at various operative stages using ordinal logistic regression. One hundred patients who underwent laparoscopic resection for colorectal cancer were analyzed. All patients were operated on by 3 surgeons at Hospital Kuala Lumpur tertiary referral center using standardized techniques and care plans assessed for operative indications. Results indicate that the prognosis factors that can explain the pathological staging of colorectal cancer were adjuvant therapy, metastasis recurrence and tumor thickness level. Pathologist may use these findings to propose guidelines for appropriate treatment plan for a particular patient according to their staging.